Association Between Seasonal Variation and Hypertension in Pregnancy at Anna Medika Madura Hospital - Novi Anggraeni; Samsiah Mat; Andriyanto Andriyanto; Rohilatul Jannah; Siti Rochimatul Lailiyah; Moh. Lutfi; Vivin Wijiastutik; Alis Nurdiana (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
Hypertension in Pregnancy are classified as follows: chronic hypertension, preeclampsia/eclampsia, chronic hypertension with superimposed preeclampsia and gestational hypertension. Hypertensive problems in pregnancy particularly pre eclampsia and eclampsia afflicts nearly 28% of pregnant women globally and are an important cause of maternal and neonatal morbidity and mortality. First-time mothers with a previous pregnancy termination, a high body mass index and a paternal effect are at a higher risk of developing pre-eclampsia. Again, Mediterranean seasonal pattern documentation showed variations in severe preeclampsia rates; all of which warrant a more comprehensive study. The purpose of this study is to analyze the relationship between seasonal variations and hypertension in pregnancy. This study used an analytical cross-sectional design. The independent variable in this study was seasonal variation, while the dependent variable was the incidence of hypertension in pregnancy. The study population consisted of 1,210 pregnant women registered in the medical records of ANNA Medika Madura General Hospital from January 1 to December 31, 2025, with a sample size of 291 pregnant women determined using the Lemeshow formula, based on the inclusion criterion of residing in Madura. . The exclusion criterion in this study was incomplete medical records and chronic hypertension . The sampling technique used stratified random sampling. Statistical analysis used chi-square test only; no adjustment for potential confounders was performed. During the dry season, 24% of pregnant women had hypertension, while 76% did not. Conversely, during the rainy season, the incidence of hypertension in pregnancy was higher than during the dry season, at 33%, with 67% of pregnant women not having hypertension. Statistical analysis results indicate a significant association between seasonal variations and the incidence of hypertension in pregnancy (p = 0.024), suggesting that the incidence of hypertension in pregnancy differs significantly between the dry season and the rainy season. Seasonal variations are significantly associated with hypertension in pregnancy, with a higher number of cases during the rainy season compared to the dry season. Healthcare providers are advised to intensify antenatal monitoring during the rainy season, particularly for pregnant women with risk factors. Strategies for prevention, early detection, and management of hypertension in pregnancy need to be further optimized. Additionally, further research is recommended to investigate the mechanisms underlying this association and to develop season-specific intervention strategies.